Penerapan Rencana Pelaksanaan Pembelajaran Anak Berkebutuhan Khusus Di Sekolah Dasar Negeri Meruya Selatan 06 Pagi: Pendahuluan, Metode Penelitian, Hasil Penelitian dan Pembahasan, Kesimpulan dan Implikasi, Referensi - Chintya Rahmawati; Asep Supena; Jaitul Hairun Nisa; Muhammad Yusuf Ferdiansyah (Jurnal Gentala Pendidikan Dasar, 2021)
This study aims to describe the implementation of the lesson plan in one of the inclusion schools, namely is Elementary School (SDN) Meruya Selatan 06 Pagi. The method used in this study is qualitative descriptive with research informants, namely special guidance teachers who teach at SDN Meruya Selatan 06 Pagi. The data in this study was obtained through two ways, namely by conducting interviews, and documentation. The results showed that teachers have implemented a learning implementation plan in accordance with the structure that accommodates planning, implementation and evaluation in learning in the school. Based on the results of the research can be concluded that in the implementation of the learning implementation plan that has been made by teachers before the learning is implemented, it has been applied very well by paying attention to the needs, advantages and disadvantages of students with special needs and students without special needs.